From Pixels to Species: A Review of Remote Sensing for Biodiversity Assessment - Mallick, Md Abu Imran (Journal of Sustainability and Environmental Management, 2025)
Remote sensing-based global biodiversity monitoring systems have transformed the field of conservation biology, enabling consistent assessment, monitoring, modelling, and reporting. These systems underpin sustainable management and informed decision-making, crucial for maintaining ecosystem health and resilience. Biodiversity monitoring is a complex process, involving multiple components that provide valuable insights into ecosystems. This review examines the significant contributions of remote sensing to biodiversity research, emphasising its potential for informing conservation decisions. Key components include biodiversity levels (genetic, species, and ecosystem), essential biodiversity variables, indicators, spatial and temporal scales, inventory, models, habitat assessment, evaluation of ecosystem services, vegetation health monitoring, and analysis of biogeochemical heterogeneity. Remote sensing through Earth Observations (EO) has revolutionised biodiversity research, offering unprecedented opportunities for monitoring ecological processes. EO technologies enable researchers to map biodiversity patterns, track changes, assess vegetation health, model species distribution and abundance, and evaluate ecosystem services. Integrating remote sensing and biodiversity science addresses pressing conservation questions, enabling researchers to develop effective monitoring strategies, improve biodiversity models, and enhance conservation outcomes.